Staphylococcus aureus endocarditis: Identifying prognostic factors using a method derived from morbidity and mortality conferences - Lefèvre, Benjamin; Legoff, Antoine; Boutrou, Mathilde; Goehringer, François; Ngueyon-Sime, Willy; Chirouze, Catherine; Revest, Matthieu; Vernet Garnier, Véronique; Duval, Xavier; Delahaye, François; Le Moing, Vincent; Selton-Suty, Christine; et al. (Frontiers in Medicine, 2022)
Objectives Lethality of Staphylococcus aureus (Sa) infective endocarditis (IE) is high and might be due to yet unidentified prognostic factors. The aim of this study was to search for new potential prognostic factors and assess their prognostic value in SaIE. Materials and methods We used a two-step exploratory approach. First, using a qualitative approach derived from mortality and morbidity conferences, we conducted a review of the medical records of 30 patients with SaIE (15 deceased and 15 survivors), randomly extracted from an IE cohort database (NCT03295045), to detect new factors of possible prognostic interest. Second, we collected quantitative data for these factors in the entire set of SaIE patients and used multivariate Cox models to estimate their prognostic value. Results A total of 134 patients with modified Duke definite SaIE were included, 64 of whom died during follow-up. Of the 56 candidate prognostic factors identified at the first step, 3 had a significant prognostic value in multivariate analysis: the prior use of non-steroidal anti-inflammatory drugs (aHR 3.60, 95%CI [1.59-8.15], p=0.002); the non-performance of valve surgery when indicated (aHR 1.85, 95%CI [1.01-3.39], p=0.046); and the decrease of vegetation size on antibiotic treatment (aHR 0.34, 95%CI [0.12-0.97], p=0.044). Conclusions We identified three potential SaIE prognostic factors. These results, if externally validated, might eventually help improve the management of patients with SaIE.